A política fiscal e a geografia econômica : um estudo sobre o crescimento econômico de municípios localizados em estados brasileiros limítrofes para o período 2003-2012 - Esquerdo, Paula da Silva (2018)
In order to study the influence of the tax industrial benefits of ICMS on the GDP growth rate, the paper approaches this issue in municipalities where, in theory, the differences in the rates of this state tax would have the greatest impact: in the municipalities present in the Brazilians states' borders. Based on counterpoints of the economic growth theories, both exogenous and endogenous, and via dynamic panel econometric modeling, the survey that included the sample of 1,159 municipalities in the country and its results showed that the tax benefits, analyzed, showed no influence significant in the real economic growth rate in the period between 2003 and 2012, being influenced only by some specific local factors such as local industrial arrangement (number of links, establishments and value added of the industry), transportation cost and demographic density.